Habitat alteration and fecal deposition by geese alter tundra invertebrate communities: Implications for diets of sympatric birds - Flemming, Scott A.; Smith, Paul A.; Kennedy, Lisa V.; Anderson, Alexandra M.; Nol, Erica (PLOS ONE, 2022)
Over the last 60 years, Arctic goose populations have increased while many sympatric tundra nesting bird populations have declined. Hyperabundant geese have well-documented effects on tundra habitats, which can alter habitat use by sympatric bird species. These habitat changes may also alter invertebrate communities and abundances, with potentially important, but as of yet, undocumented effects on insectivorous birds such as shorebirds. Here, we determined the effects of goose-induced habitat alteration on invertebrate communities and relate the observed changes to shorebird diet. At sites and habitat types representing a gradient of goose influence, we identified goose-related changes in ground cover and linked these factors to variation in invertebrate communities. We then used DNA metabarcoding to characterize the diet of six shorebird species across sites and identify inter-site variation in abundance, biomass, and timing of emergence of dominant shorebird prey items. Invertebrate diversity and richness did not vary either among sites or habitat types. However, for prey items identified as part of the shorebird diet, we found significantly higher abundances and biomasses at a moderately goose-influenced site than at either low or high goose-influenced sites. Biomass of Tipulidae, the dominant prey taxon for shorebirds at the study sites, was 7.5 times higher at the moderately goose-influenced site compared to the site where goose influence was minor. We attribute this enhancement of prey biomass to both the fertilizing effect of goose fecal pellets and the moderate grazing pressure. Many studies have documented adverse effects of overabundant geese, but here we show that a moderate degree of goose grazing can lead to enhanced biomass of invertebrates, with the potential for improved shorebird foraging success and chick growth. These benefits, however, might be outweighed by negative effects of goose-induced habitat alteration and predation pressure.